Synthesis, characterization and high pressure propene oligomerization over heteropoly acids, SAPO-11 molecular sieves and MeAPSO-11 molecular sieves - Vaughan, James Stuart (Department of Chemical Engineering, 2016)
Bibliography: pages 219-232.